First record of genus Orbiniella Day, 1954 (Polychaeta: Orbiniidae) in North Atlantic Ocean with the description of a new species - Parapar, Julio; Moreira, Juan; Helgason, Gudmundur Vidir (Zootaxa, 2015)
A new species of the genus Orbiniella Day, 1954 (Polychaeta: Orbiniidae), collected during the BIOICE programme on sedimentary bottoms off Iceland, is described. Orbiniella petersenae sp. nov. is a shelf and slope species (107 to 1,915 m) chiefly characterized by having notopodial postchaetal papilla from first chaetiger, long crenulated capillary chaetae and several acicular chaetae on each parapodial rami, and pygidium with four lobes. External micromorphology and gross internal anatomy were studied using, respectively, SEM and micro-CT; this is the first time these techniques are used for any species in this genus. A key to all species of this genus worldwide is provided.